2012
DOI: 10.1186/1741-7015-10-122
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in periodontitis patients and gingival fibroblasts: unraveling the link between chronic diseases and inflammation

Abstract: BackgroundPeriodontitis, the most prevalent chronic inflammatory disease, has been related to cardiovascular diseases. Autophagy provides a mechanism for the turnover of cellular organelles and proteins through a lysosome-dependent degradation pathway. The aim of this research was to study the role of autophagy in peripheral blood mononuclear cells from patients with periodontitis and gingival fibroblasts treated with a lipopolysaccharide of Porphyromonas gingivalis. Autophagy-dependent mechanisms have been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 38 publications
8
116
0
1
Order By: Relevance
“…Furthermore, kidney, brain and liver contain the highest endogenous levels of CoQ 10 [14]. The findings of the present study show that lipophilic antioxidants such as CoQ 10 and vitamin E ameliorated mitochondrial dysfunction, oxidative stress and reduced cell death with a more specific interaction with mitochondrial biogenesis, which is not observed in hydrophilic antioxidants such as NAC or BHA. Since CoQ 10 is a pivotal element in mitochondrial respiratory chain and, at the same time, is an important antioxidant, these results suggest that mitochondrial dysfunction is crucial in the pathophysiology of periodontal disease and CoQ 10 could be a therapeutic option in bacterial LPS infection, sepsis or other similar conditions.…”
Section: Mitochondrial Dysfunction Provoked By P Gingivalis Lps Is Rmentioning
confidence: 37%
See 1 more Smart Citation
“…Furthermore, kidney, brain and liver contain the highest endogenous levels of CoQ 10 [14]. The findings of the present study show that lipophilic antioxidants such as CoQ 10 and vitamin E ameliorated mitochondrial dysfunction, oxidative stress and reduced cell death with a more specific interaction with mitochondrial biogenesis, which is not observed in hydrophilic antioxidants such as NAC or BHA. Since CoQ 10 is a pivotal element in mitochondrial respiratory chain and, at the same time, is an important antioxidant, these results suggest that mitochondrial dysfunction is crucial in the pathophysiology of periodontal disease and CoQ 10 could be a therapeutic option in bacterial LPS infection, sepsis or other similar conditions.…”
Section: Mitochondrial Dysfunction Provoked By P Gingivalis Lps Is Rmentioning
confidence: 37%
“…For this, mitochondrial biogenesis and mitophagy are two pathways that regulate mitochondrial content and metabolism preserving homeostasis. Recently, we described reduced levels of CoQ 10 and mitochondrial chain complex induced by LPS [2] and active autophagic processes in blood cells from periodontitis patients and activated in fibroblasts after P. gingivalis LPS [10]. To assess the functional consequences of decreased respiratory chain enzyme activities and CoQ 10 levels, we determined ATP levels as an indicator of cellular bioenergetics and well-being status.…”
Section: Mitochondrial Biogenesis Impairment Induced By Lps Is Restormentioning
confidence: 99%
“…It is postulated that selective autophagy of mitochondria, known as mitophagy, contributes to the maintenance of mitochondrial quality by eliminating dysfunctional or damaged mitochondria 38 . Oxidative stress has been shown to induce autophagy, 38 and a recent study demonstrated an enhancement of autophagy mediated by mitochondrial ROS in peripheral blood mononuclear cells from patients with periodontal disease 39 . This also supports the hypothesis that mitochondrial function is essential in inflammation‐related disease, including periodontal disease.…”
Section: Discussionmentioning
confidence: 54%
“…The production of these molecules by the accompanying community may facilitate iron acquisition by the 'red-complex. ' Finally, genes involved in stress tolerance were highly over-represented in a large fraction of the community and their upregulation may be related to the production of reactive oxygen species during disease (Wright et al, 2011;Bullon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%